Engineering Psychology and Cognitive Ergonomics 9th International Conference, EPCE 2011, Held as Part of HCI International 2011, Orlando, FL, USA, July 9-14, 2011. Proceedings - Harris, Don.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 9th International Conference on Engineering Psychology and Cognitive Ergonomics, EPCE 2011, held in Orlando, FL, USA, in July 2011, within the framework of the 14th International Conference on Human-Computer Interaction, HCII 2011, together with 11 other thematically similar conferences. The 67 full papers presented were carefully reviewed and selected from numerous submissions. The papers are organized in topical parts on cognitive and psychological aspects of interaction; cognitive aspects of driving; cognition and the Web; cognition and automation; security and safety; and aerospace and military applications.
Keywords: Computer science; Information systems; Artificial intelligence; Computer simulation; Education; Consciousness; Computer Science; Artificial Intelligence (incl. Robotics).; User Interfaces and Human Computer Interaction; Simulation and Modeling; Information Systems Applications (incl.Internet).; Cognitive Psychology; Computers and Education